2013
DOI: 10.1371/journal.pone.0073579
|View full text |Cite
|
Sign up to set email alerts
|

A Toolbox for Tuberculosis (TB) Diagnosis: An Indian Multicentric Study (2006–2008). Evaluation of QuantiFERON-TB Gold in Tube for TB Diagnosis

Abstract: BackgroundThe aim of this multicentric prospective study in India was to assess the performance of the QuantiFERON TB-Gold in tube (QFT-GIT), Tuberculin Skin Test (TST) and microbiological results as additional tools for diagnosing active tuberculosis (TB) and latent infection (LTBI) according to Human Immunodeficiency Virus (HIV) status.MethodsIndividuals with and without active TB and HIV infection were enrolled between 2006–2008. QFT-GIT and TST results were analyzed per se and in combination with microbiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 30 publications
3
9
1
Order By: Relevance
“…Although T-SPOT.TB showed higher sensitivity than QFT-GIT, a relative increase of 12%, there was no statistical evidence of a difference in sensitivity. The sensitivity of QFT-GIT in the IDEA study was lower than that in other recent studies [29][30][31] (see Appendix 11, Table 74).…”
Section: Comparison Of Diagnostic Accuracy Of T-spottb and Quantifercontrasting
confidence: 60%
“…Although T-SPOT.TB showed higher sensitivity than QFT-GIT, a relative increase of 12%, there was no statistical evidence of a difference in sensitivity. The sensitivity of QFT-GIT in the IDEA study was lower than that in other recent studies [29][30][31] (see Appendix 11, Table 74).…”
Section: Comparison Of Diagnostic Accuracy Of T-spottb and Quantifercontrasting
confidence: 60%
“…This is most likely due to the fact that these two populations of ATB patients were similar regarding their HIV status, as previously reported [46], [47].…”
Section: Discussionsupporting
confidence: 71%
“…[ 29 ] and in India by Lagrange et al . [ 30 ], where the T-cell IFN-γ responses did not correlate with several measures of the bacterial yield in the sputum of the PTB patients at diagnosis, including SM status and grade, and time to positivity of the liquid culture.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study carried out in India has shown that the cumulative results of the smear microscopy and the 2 immunological tests improved the detection rate of ATB [ 30 ]. Similarly, our study shows a cumulative sensitivity of 97.5% with an increase of the LR for the negative test (9.2), indicating that such triple association may rule out PTB in those who are negative for all 3 tests.…”
Section: Discussionmentioning
confidence: 99%